PENINGKATAN AKTIVITAS BELAJAR SISWA DALAM MATA PELAJARAN SENI BUDAYA MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE QUANTUM LEARNING DI KELAS VII SMPN 13 PADANG - ermayetti ermayetti (JURNAL MANAJEMEN PENDIDIKAN, 2017)
Based on the learning activities of students of Class VII SMPN 13 Padang in Arts subjects Budayaditemukan that the learning activities of students in the subjects of art Budayamasih very low. The purpose of this study is to describe and obtain information about the Enhanced Learning Activities Arts students in subjects Budayamelalui cooperative learning model Quantum Learning in Class VII SMPN 13 Padang of West Sumatra Province.This research is a class act. The procedure in this research include planning, action, observation and reflection. The study consisted of two cycles of the four meetings. Subject of the study consisted of 32 students of class VII SMPN 13 Padang. Data were collected by using observation sheet. Data were analyzed using percentages.Based on the results of research and discussion that has been stated in the previous chapter, it can be concluded that it can be concluded that the model pembelajaan demonstration can improve students' learning activities in the subjects of Arts and Culture in SMPN 13 Padang. Activities of students in the first cycle was 71.71 (enough) increased to 76.63 (good) with an increase of 9.82.